Navigability on the websites of the university CRAI: a methodological proposal for improvement - Pérez Montoro, Mario (2013)
In the last decade, the university library has undergone a number of important changes. From being considered a classic university service, it is becoming a reference centre for the correct functioning of university teaching and research; it is now called CRAI (Resource Centre for Learning and Research). The CRAI website has become one of the priority routes for the provision and management of these critical resources and services. However, different studies show a clear general downward trend in the use of this type of website by the university community. This downward trend in the use of these types of websites can be reversed by making improvements to their architectural structure and, in particular, by optimising their navigation systems. The purpose of this work is to offer a methodology for the design of this type of systems that combines expert analysis (based on heuristics, parameters and indicators) with User-Centered Design (UCD) techniques.